3D printing of fine alumina powders by binder jetting. Issue 10 (August 2021) - Mariani, Marco; Beltrami, Ruben; Brusa, Paolo; Galassi, Carmen; Ardito, Raffaele; Lecis, Nora
Graphical abstract: Abstract: Additive manufacturing of ceramics is still at an early-development stage; however, the huge interest in custom production of these materials has led to the development of different techniques that could provide highly performing devices. In this work, alumina (α-Al2 O3 ) components were produced by binder jetting 3D printing (BJ), a powder-based technique that enables the ex-situ thermal treatment of the printed parts. The employment of fine particles has led to high green relative density values (>60 %), as predicted by Lubachevsky-Stillinger algorithm and DEM modelling. Then, extended sintering has been observed on samples treated at 1750 °C that have reached a final density of 75.4 %. Finally, the mechanical properties of the sintered material have been assessed through bending test for flexural resistance and micro-indentation for Vickers hardness evaluation.